The convenient preparation of stable aryl-coated zerovalentiron nanoparticles; Beilstein Journal of Nanotechnology; № 6 - Guselnikova O. A. Olga Andreevna; Galanov A. I. Andrey I.; Gutakovskii A. K. Anton K.; Postnikov P. S. Pavel Sergeevich (2015, 2015)
Title screen